2014
DOI: 10.1155/2014/384583
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of a Hypersaline Sodium-Rich Naturally Sparkling Mineral Water to the Protection against Metabolic Syndrome Induction in Fructose-Fed Sprague-Dawley Rats: A Biochemical, Metabolic, and Redox Approach

Abstract: The Metabolic Syndrome increases the risk for atherosclerotic cardiovascular disease and type 2 Diabetes Mellitus. Increased fructose consumption and/or mineral deficiency have been associated with Metabolic Syndrome development. This study aimed to investigate the effects of 8 weeks consumption of a hypersaline sodium-rich naturally sparkling mineral water on 10% fructose-fed Sprague-Dawley rats (Metabolic Syndrome animal model). The ingestion of the mineral water (rich in sodium bicarbonate and with higher p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 65 publications
5
49
0
1
Order By: Relevance
“…Metabolic syndrome is described the group of character of quite a lot of metabolic abnormalities, based on hyperlipidemia, abdominal obesity and insulin resistance [2]. This disorder is accompanied with an increase in serum insulin, leptin hormone and the possibility for atherosclerotic cardiovascular disease and type 2 diabetes mellitus [3]. Research indicated that in fructose-fed rats (FFR) circulating triglyceride, the weight of liver, abdominal adipose tissue, and insulin resistance (IR) increased that was accompanied with impaired glucose tolerance [4].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome is described the group of character of quite a lot of metabolic abnormalities, based on hyperlipidemia, abdominal obesity and insulin resistance [2]. This disorder is accompanied with an increase in serum insulin, leptin hormone and the possibility for atherosclerotic cardiovascular disease and type 2 diabetes mellitus [3]. Research indicated that in fructose-fed rats (FFR) circulating triglyceride, the weight of liver, abdominal adipose tissue, and insulin resistance (IR) increased that was accompanied with impaired glucose tolerance [4].…”
Section: Introductionmentioning
confidence: 99%
“…After a 10-day acclimatization period, animals were randomly divided into three groups (seven animals each) with free access to pellet food and different drinking solutions, for 8 weeks: a) tap water (CONT), b) 10% fructose in tap water (FRUCT) or c) 10% fructose in natural mineral-rich water (FRUCTMIN). A 3-week pretreatment period with the natural mineral-rich water was performed to the FRUCTMIN group (while the other rats drank tap water) to allow adjustment to water flavor and sparkles [10,12].…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…The chemical characteristics of tap and natural mineral-rich waters are already described [10,12]. The latter [classified as a hypersaline sodium-rich naturally sparkling mineral water in conformity with the European Community Council guidelines for natural mineral waters (2009/54/EEC)] has high total mineralization content (2855 mg/L), is mainly rich in sodium and bicarbonate, and has a higher potassium, calcium and magnesium content than the former.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize stress-induced variations only data from the last 10 min from each 30 min were average for analysis. If difference between SBP and DBP fell below 20 mmHg and/or HR rose above 350 beats/min, blood pressure measurements were considered unreliable [17]. To withdraw the effect of movement in blood pressure measurements, data was only used when locomotor activity in the animal cage was blunted.…”
Section: Data Acquisitionmentioning
confidence: 99%